Management of pancreatitis and pancreatic: fluid collections - Kahaleh, Michel (2018)
Acute pancreatitis is a constant management challenge, especially with peripancreatic collection that are one of the most common complications; after the first surgical attempts that had high mortality, there had to be a new approach based in decades of acquired knowledge in physiopathology added to the development of endoscopic intervention techniques and the evolution of endoscopic devices help to establish less invasive and conservative management. This review allows us to know the last advances in the management of acute pancreatitis, pancreatic pseudocyst and walled off necrosis, determined the right time for the management to become more invasive, even considering surgery at a final stage. It also reviews the different types of drainage of peripancreatic collections and the accessories currently in use.